Pemberdayaan Kelompok Tani Hutan Sumber Abadi melalui Inovasi Teknik Pembibitan Porang - Hidayat, Ramdan; Purwadi, Purwadi; Sasongko, Purnomo Edi (Universitas Sebelas Maret, 2022)
Empowerment of Sumber Abadi Forest Farmer Groups through Innovation of Porang Nursery Techniques. Forest Farmers Group (FFG) Sumber Abadi is located in Panglungan Village, Wonosalam District, Jombang Regency, whose area is 500-750 m asl and daily temperature of 20° C. The conditions of socio-economic need to be improved, considering that their livelihoods depend on forest products and half of the population belongs to the category of pre-prosperous families. Panglungan village has the largest porang area and has the potential for a profitable porang seed business, encouraging farmers to carry out traditional nurseries to fulfill the increasing demand for seeds. Porang is a super strategic commodity and prospectus as a healthy food, low carbohydrates and high fiber, and a high tuber selling price (Rp 10,000,-/kg). Obstacles in the porang nursery business in Panglungan Village, namely: (1) lack of understanding of proper nursery techniques, (2) weak innovation of porang nurseries, (3) lack of understanding of seed supply chain management, and (4) weak of institutional functioning. The aim of the activity is to increase empowerment through innovative porang nursery techniques. Empowerment methods include: (1) training on innovation in porang nursery technology on various seed sources, (2) demonstration plots for porang nurseries, (3) economic empowerment of rural communities, (4) training on marketing porang seeds online. The results of the empowerment of FFG Sumber Abadi showed that there were 2 groups of porang seed breeders who were innovative in seeding techniques and marketing with a volume of more than 2 million seeds that lasted for 5 months.